THE IMPLEMENTATION THINK PAIR SHARE (TPS) TO IMPROVE STUDENTS’ SPEAKING SKILL OF SMK BARAMULI PINRANG - Rasmah Nursira; Mariani Mariani; Ayu Ashari (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2026)
The purpose of the research was to find out whether or not the application of Think Pair Share (TPS) Technique may increase the students to speaking up about recount text content. The study employed mix-method design with two groups pretest and post-test design. The TPS technique was the independent variable, and the students' interest and speaking ability were the dependent factors. The sample of this research was 37 students from 2 classes selected from the population of 10th grade students, where each class had 14 students. The Speaking Test is the tool used in this study. The conclusion of the data analysis shows that students' writing skills have increased dramatically. This is revealed by the average score of the pre-test, which is 27.50 and the post-test, which is 61.07. This shows that the application of the Think Pair Share (TPS) strategy can improve students' speaking skills on the Recount test material. After analyzing the data quantitatively, the t-test value exceeds the t-table for the post-test, which is 6.711 exceeding 1.761. The conclusion is that the TPS technique improves students' competence in speaking recount texts in grade 10 of SMK Baramuli Pinrang.